The Bahamas : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 1999)
This Selected Issues paper and Statistical Appendix summarizes the evolution of monetary institutions in The Bahamas. It discusses the framework in which monetary policy is conducted in the country. Following a brief description of the evolution of institutions, the paper summarizes the monetary policy objectives and constraints of the central bank, and assesses the instruments to achieve these objectives. The paper concludes that the central bank has been able to use interest rate changes, selective credit controls, and moral suasion to achieve its monetary objectives.